Population dynamics in colonizing vancomycin-resistant Enterococcus faecium isolated from immunosuppressed patients. (March 2022) - Both, Anna; Kruse, Florian; Mirwald, Nadine; Franke, Gefion; Christner, Martin; Huang, Jiabin; Hansen, Jan Lennart; Kröger, Nicolaus; Berneking, Laura; Lellek, Heinrich; Aepfelbacher, Martin; Rohde, Holger
Highlights: Intestinal vancomycin-resistant enterococci (VRE) populations can show high heterogeneity in individual patients. The VRE population structure can undergo important dynamic changes over the course of weeks. Mobilization of van-element–carrying plasmids appears to be an important factor in the inter-clonal spread of vancomycin resistance. VRE population heterogeneity appears more pronounced in at-risk patients exposed to antibiotics. ABSTRACT: Objectives: Vancomycin-resistant Enterococcus faecium and Enterococcus faecalis (VRE) are a common cause of healthcare-associated infections. Whole genome sequencing–based typing methods yield the highest discriminatory power for outbreak surveillance in the hospital. We analysed the clonal composition of enteric VRE populations of at-risk patients over several weeks to characterise VRE population diversity and dynamics. Methods: Five bone marrow transplant recipients (three colonised with vanA -positive isolates, two colonised with vanB -positive isolates) contributed three rectal swabs over a course of several weeks. Fourteen VRE colonies per swab were analysed by core genome multi locus sequence typing (cgMLST) and typing of the van -element. Results: VRE populations were clonally diverse in three of five patients, and population composition changed dynamically over the time of observation. Besides new acquisition of VRE isolates, shared van -elements localised on nearly identical plasmids between clonally different isolates indicate horizontal gene transfer as a mechanism behind VRE population diversity within single patients. Conclusion: Outbreak detection relies on typing of isolates, usually by analysing one isolate per patient. We here show that this approach is insufficient for outbreak surveillance of VRE in highly vulnerable patients, as it does not take into account VRE population heterogeneity and horizontal gene transfer of the resistance element.